2016
DOI: 10.1007/s00300-016-1907-0
|View full text |Cite
|
Sign up to set email alerts
|

Low organotin contamination of harbour sediment in Svalbard

Abstract: Arctic sea routes are opening up for maritime transport due to sea ice retreat leading to increasing human activities in the Arctic and concomitant pressures on the environment. Organotin compounds are used in antifouling paints of large seagoing vessels and are known to leach into the marine environment and accumulate in sediments and biota. As organotin levels in Svalbard sediments have not been documented in peer-reviewed literature before, this study describes the levels in sediment of harbours around Sval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Organotin compounds used in antifouling paints of large seagoing vessels leach into the marine environment and accumulate in sediments and biota. Organotin levels in sediments of Svalbard harbours are still low (below the detection limit up to 14 ng Sn g -1 dw sum-butyltin) compared to other Arctic regions with a longer history of shipping (Van Heuvel-Greve et al 2016). However, contaminant levels in Kongsfjorden should be monitored and mitigation measures put into action if they increase.…”
Section: Partmentioning
confidence: 95%
“…Organotin compounds used in antifouling paints of large seagoing vessels leach into the marine environment and accumulate in sediments and biota. Organotin levels in sediments of Svalbard harbours are still low (below the detection limit up to 14 ng Sn g -1 dw sum-butyltin) compared to other Arctic regions with a longer history of shipping (Van Heuvel-Greve et al 2016). However, contaminant levels in Kongsfjorden should be monitored and mitigation measures put into action if they increase.…”
Section: Partmentioning
confidence: 95%
“…Increased visitation by the public through ecotourism, scientific expeditions, the mining industry and shipping traffic puts the area at risk of both direct and indirect human impacts (e.g. Van den Heuvel-Greve et al, 2016;Wiencke & Hop, 2016;Renaud et al, 2015). In Svalbard, alien species are most likely to be introduced via biofouling of ship hulls (e.g.…”
Section: Objectivesmentioning
confidence: 99%
“…Chen et al ( 2010 ) found that an elevated concentration of Fe, Mn, and Zn was found in Daya Bay, China, probably due to improper treatment of industrial effluent. On the other hand, van den Heuvel-Greve et al ( 2016 ) detected organotin was present in sediment and suggested to continue monitoring contaminated levels in Coles Bay, Svalbard. Generally speaking, the degraded estuaries have common characteristics: deteriorated coastal vegetation, hardened shoreline, and sediment/turbidity influx (Kennish 2012 ).…”
Section: Introductionmentioning
confidence: 99%